A STUDY ON FINANCIAL PERFORMANCE OF REGIONAL RURAL BANKS (RRBS) OF INDIA (International Journal of Food and Nutritional Sciences, 2022)
This research paper worked on measuring Financial Performance of Regional Rural Banks of India. Regional Rural Banks are the banking organizations being operated in different states of India. They have been created to serve the rural areas with banking and financial services. Rural banking institutions are playing a extremely imperative part for adaptable expansion of rural areas of the nation. In order to support the rural banking sector in recent years, Regional Rural Banks have been set up all over the country with the objective of meeting the credit needs of the most under privileged sections of the society. This research aim is that to analyze the financial performance of RRBs based on the Deposit ,Credits and Credit- Deposit Ratio. The study is based on secondary data collected from RRBs websites, reports of the bank, magazines, journals, documents & other published information. The study covers the period of six years i.e. 2016-2022.The Statistical Tools like Mean and Standard Deviations is used to analyse the data and Minimum and Maximum have also been deployed to analyse the data.